The use of lateral flow immunoassays for the detection of fentanyl in seized drug samples and postmortem urine. Issue 2 (4th December 2020) - Angelini, Daniel J.; Biggs, Tracey D.; Prugh, Amber M.; Smith, Jessica A.; Hanburger, Jennifer A.; Llano, Bob; Avelar, Raquel; Ellis, Angela; Lusk, Brady; Malik Naanaa, Abdallah; Sisco, Edward; Sekowski, Jennifer W.
Abstract: The opioid crisis has continued to progress in the United States and the rest of the world. As this crisis continues, there is a pressing need for a rapid and cost‐effective method for detecting fentanyl. Recent studies have suggested that lateral flow immunoassays (LFIs) could fill this technology gap. These qualitative paper‐based assays contain antibodies designed to react with fentanyl and provide positive or negative results within a matter of minutes. In this study, two different LFI configurations for the detection of fentanyl were examined (dipsticks and cassettes) for effectiveness of detection using seized drug samples and postmortem urine samples. In the current study, 44 seized drug samples (32 fentanyl‐positive, 12 fentanyl‐negative) and 14 postmortem urine samples (10 fentanyl‐positive, 4 fentanyl‐negative) were analyzed. All 32 fentanyl‐containing seized drug samples and 10 postmortem fentanyl‐positive urine samples displayed positive LFI results with both LFI configurations. The fentanyl dipsticks displayed a sensitivity of 100%, a specificity of 75%, and an efficiency of 93.2% for seized drug samples and a sensitivity, specificity, and efficiency of 100% for postmortem urine. Analysis of the fentanyl cassettes displayed a sensitivity, specificity, and efficiency of 100% for seized drug samples and a sensitivity of 100%, a specificity of 75%, and an efficiency of 92.9% for postmortem urine samples. These data point to the utility of LFIs as a quick and low resource‐dependent option for presumptive detection of fentanyl in real‐world situations.